(Re)descobrindo a cozinha quilombola: estudo na comunidade Vovó Izabel em Nova Palma - RS - Raddatz, Walter Corrêa (2024)
This research was presented to the Master's course in Cultural Heritage, History and Cultural Heritage research line at the Federal University of Santa Maria. The objective was to map the knowledge and practices of quilombola cuisine through the recipe book, as a driver of recognition of cultural heritage in the region of Quarta Colônia, in the interior of the State of Rio Grande do Sul, in the quilombola community Vovó Izabel in Nova Palma – RS . This way, by studying the aforementioned quilombola habits in the region, you will be able to learn more about the history, culture and quilombola traditions present in the region, providing them with the recognition they deserve. To this end, the research problem of this research sought to investigate: How does the transmission of quilombola knowledge and culinary knowledge occur in the Vovó Izabel quilombola community in Nova Palma-RS? Methodologically, a qualitative approach was used in addition to the methodology of autobiographical narratives, that is, oral history, using technical instrumentation, semi-structured interviews and application of questionnaires. As a result, it became clear that the transmission of such knowledge is carried out within the family divided with the community that shares the same cultural bases and the same cultural identity. Furthermore, it is agreed that quilombola gastronomy can be an alternative capable of perpetuating history, valuing the community's intangible heritage, and promoting gastronomic tourism in the region. Using the data obtained through the research, a book was created with typical recipes from quilombo residents, the true objective and product of this dissertation.